Use of Common Inflammatory Markers in the Long-Term Screening of Total Hip Arthroprosthesis Infections: Our Experience - Gabriele Falzarano; Antonio Piscopo; Predrag Grubor; Giuseppe Rollo; Antonio Medici; Valerio Pipola; Michele Bisaccia; Auro Caraffa; Elizabeth Mary Barron; Francesco Nobile; Raffaele Cioffi; Luigi Meccariello (Advances in Orthopedics)
Orthopedic implants have become essential components of modern medicine. The risk of infection of total hip arthroplasty (THA) is 1.5%−2%. Are the C-reactive protein (CRP), the erythrocyte sedimentation rate (ESR), and procalcitonin (PCT) good markers for THA infection screenings? From February 2009 to December 2012 at our Department of Orthopedics and Traumatology, 1248 patients were treated with THA. No prosthesis was cemented. All patients received antibiotic prophylaxis. All patients were discharged approximately 7.4 days after surgery with this clinical and radiographic follow-up program at 15 days and 1, 3, 6, 12, 24, and 36 months after surgery. Blood samples to determine ESR, CRP, and PCT values were taken at 1 hour before surgery and 15 days and 1, 3, 6, 12, 24, and 36 months after surgery. During follow-ups there were 22 cases of THA infections; according the Widmer classification, infections are hematogenous ones in 16 cases, late chronic ones in 5 cases, and early postoperative ones in 1 case. In all cases the three markers were considered positive; in 6 cases there were no radiological signs of septic loosening. ESR, CRP, and PCT proved to have a greater diagnostic accuracy than X-rays in predicting late chronic and early postoperative infections. These markers are valuable support for the surgeon in monitoring the prosthetic implant lifespan.